PENGARUH RASIO KEUANGAN INDIKATOR KESEHATAN BANK PADA PRICE EARNING RATIO PERUSAHAAN PERBANKAN - Sari, Citra Kartika; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 13 No 1 (2015), 2015)
The main purpose of the establishment of a company regardless of the type of business is to maximize shareholder wealth, or to maximize the company's stock price therefore presents the company's financial statements to provide information about the health condition of the company for the stakeholders. This study aimed to determine the effect of financial ratios health indicators banking on price earnings ratio of the banking company. This research was conducted on banking companies listed on the Stock Exchange on LQ45 2009-2013. The number of samples taken 64 banking companies, with saturated sample method. Data collection was done by non-participant observation. The analysis technique used is multiple linear regression. Based on the analysis found a positive effect on the variable CAR PER. ROA, NPL and LDR does not affect the PER in the banking companies listed on the Stock Exchange on LQ45 2009-2013.
Keywords: Financial Ratios, CAMEL, Price Earning Ratio